A Comparative Study of Knowledge and Beliefs on Climate Change Among Teachers in India and the United States - Shimray, Chong; Padmanabhan, Jubilee; Pragya (SCHOOL SCIENCE, 2021)
Climate change is a major concern globally due to the unprecedented increase in environmental degradation due to unsustainable production, consumption, disposal, transportation, etc., resulting in environmental changes in the form of global warming and the chain of impacts it has on the atmosphere, oceans, life, livelihood, health, agriculture, etc. It is a threat not only to the human population but also to all the creatures on the planet Earth. The impact of climate change is manifested in various forms such as heavy rain and flood, flash floods, earthquake, severe drought, more intense cyclones, extreme summers and winters, acid rain, to list a few. The present paper aims to compare the knowledge and beliefs on climate change of teachers with respect to their country of origin, level of teaching and the subject they teach. It also explores whether knowledge on climate change is a predictor of beliefs on climate change and vice versa. The data was collected from teachers teaching in the schools of India and the United States, i.e., 1013 teachers who were teaching in India and 323 teachers teaching in the United States. The data was collected using a knowledge test on climate change and a scale on beliefs on climate change. The data was analysed using statistical tool and is presented in the paper. The findings will provide a baseline information about the professional development programmes that can be taken up for teachers and at the same time give some direction to the curriculum developers and policy makers while taking decisions.